PERUBAHAN VIABILITAS DAN STRUKTUR SUBSELULER SPERMATOZOA DOMBA SETELAH PENGERINGBEKUAN - Takdir Saili; I Ketut Mudite Adnyana; Ronny Rachman Noor; Mohamad Agus Setiadi; Srihadi Agungpriyono; Arief Boediono (Jurnal Veteriner, 2009)
Several methods i.e. cooling, freezing, and freeze-drying have been widely used to preserve spermatozoa with various degree of success. Freeze-drying appears to provide a method to preserve spermatozoa in a dry state without requiring liquid nitrogen for storing frozen spermatozoa. Freeze-drying procedures can have a detrimental effect on plasma membrane and acrosomal cap of the spermatozoa. In this experiment study, the viability and subcellular changes of freeze-dried ram spermatozoa were evaluated using staining method and scanning electron microscopy. The results revealed that all freeze-dried spermatozoa were dead following evaluation using eosin staining and Hoechst-propidium iodide staining methods. Morover, plasma membrane and acrosomal cap of freeze-dried ram spermatozoa was disrupted observed using scanning electron microscope.